Circlulation of tumor cells and their effect on breast cancer: reviewing the results of previous studies - Marinko, Tanja; Lah Turnšek, Tamara; Serša, Gregor (Onkologija : Slovenian Journal of Oncology, 2011)
Circulating tumor cells (CTCs) are epithelial tumor cells detected in the peripheral blood of patients with solid malignant tumors. They originate from the primary tumor or metastatic sites. New techniques have been developed to isolate and characterise these cells, including the FDA-approved Cell-Search, which are using mainly cytometric/antibody-based and molecular approaches. Recent advances in theories regarding metastasis support the role of early release of tumor cells in the neoplastic process. It has been found that phenotypic variation exists between the primary tumor and CTCs. Of particular interest is the difference found between primary tumor and CTC HER-2 status in both metastatic and early breast cancer. CTC enumeration has been incorporated into different fields of oncology as a prognostic marker, a tool to monitor therapy response, and a method to understand basic tumor characteristics. But currently, there is still no role for CTCs in clinical practice.